Class I Integron and Î²-lactamase encoding genes of multidrug resistance Salmonella isolated from pigeons and their environments - Yousef, S.; Mamdouh, R. (Cellular and Molecular Biology, 2016)
Seroprevalence of Salmonella spp. was investigated in pigeon and its surrounding environment of Sharkia province, Egypt. Samples were randomly collected from fifty freshly dead squabs, forty freshly dead adults pigeons, sixty diseased adult pigeons and 100 apparently healthy adult pigeons. Bacterial isolates were tested for their susceptibility to 17 different antimicrobial discs, by using the disc diffusion method. The bacterial isolates were tested for Class I and Î²-lactamase encoding genes by using PCR. In vitro sensitivity of all Salmonella isolates were completely resistant to Streptomycin, Amoxicillin, clavulanic acid, Amoxicillin, Ampicillin and Ceftazidime (100%). Class1 integron were characterized in 70% Salmonella isolates from squabs, 42.9 % in adult pigeons and 14.3% in pigeon environment which confer their resistance to streptomycin and ampicillin. Meanwhile TEM-1 Î²-lactamase was characterized in 20% of tested Salmonella isolates from squabs including S. Entertidis, 42.9% of tested Salmonella isolates from adult pigeons including S. Entertidis which confer their resistance to cephalosporin and not detected in all isolates from pigeons environments. In conclusion TEM-1 Î²-lactamase was characterized in 20% of Salmonella isolates from squabs while Class1 integron was characterized in 70% Salmonella isolates from squabs.